Context-aware information in mobile devices - Ferreira, J. C. (2019)
This paper describes a novel approach for indoor location and integration of other services in a university campus using Bluetooth Low Energy (BLE) devices. These BLE devices broadcast a Bluetooth signal in a limited and configured range/area, thus functioning as beacons that provide useful context-aware information to nearby devices operating with custom applications. Such applications can interpret the received signals as location and provide a range of useful services to the end user (students, events attendees), namely, indoor location and navigation or personalized complex workflows that require the interaction of the end user with multiple services within the university campus.